Varieties of Capitalism (VoC) and Varieties of Distributions (VoD): How Welfare Regimes Affect the Pre- and Post-Transfer Shapes of Inequalities? - Louis Chauvel; Eyal Bar-Haim (Luxembourg Income Study (LIS), 2016)
In comparative analysis, we know that shape of income distribution are variable and broadly related to typesf welfare capitalism. Here, we expand on the socio-economic regimes literature and show almost perfect similarity between varieties of capitalism (VoC) and varieties of distributions (VoD). Utilising a new tool for income analysis, the isograph, and when we consider three stages of distributions by country-period: 'before' taxes and redistributions, 'after' (equivalized disposable of incomes) and the shape of 'effort' between, the empirical clustering of countries are strongly related to what is theoretically known of welfare capitalism. We extend this relation to over 30 countries (LIS datasets) and then compare transformations over time, and then to the 183 LIS datasets having pre and post transfer incomes. We specifically detect, in particular in the lower percentiles of Nordic countries, but in other countries too, an increasing problem of massive inequality 'before': a strong decline of market incomes at the bottom of the distribution is balanced by more generous transfers, but the risk is to generate poverty and dependence traps that contradicts the initial concept of the Social-Democratic welfare regime.
Keywords: 330